Silver-assisted gold-catalyzed formal synthesis of the anticoagulant Fondaparinux pentasaccharide - Gulab Walke (Nature Portfolio, 2021)
Despite strong demand for their clinical use, the synthesis of heparin oligosaccharides as anticoagulants remains challenging. Here, a mild and scalable formal synthesis of Fondaparinux pentasaccharide is presented through [Au]/[Ag]-catalyzed glycosidations.